2022
DOI: 10.3389/fpsyg.2021.710140
|View full text |Cite
|
Sign up to set email alerts
|

How Do Nepotism and Favouritism Affect Organisational Climate?

Abstract: This study seeks to determine the effect of nepotism and favouritism on organisational climate. Using the method of random sampling, 269 persons working in Lithuanian organisations were surveyed. The received data was analysed via the application of the methods of correlation and linear regression. It was determined that organisational climate is influenced significantly by variables such as the manager’s behaviour, safety and relationships with employees, values and traditions, communication, sharing of infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…3. Chaxu climate, this paper refers to Vveinhardt and Bendaraviciene (2022), three items were taken to measure the organizational Chaxu atmosphere by the reliability test. 4.…”
Section: Questionnaire Designmentioning
confidence: 99%
See 1 more Smart Citation
“…3. Chaxu climate, this paper refers to Vveinhardt and Bendaraviciene (2022), three items were taken to measure the organizational Chaxu atmosphere by the reliability test. 4.…”
Section: Questionnaire Designmentioning
confidence: 99%
“…The organizational climate of Chaxu is an organizational climate in which individuals treat members of the organization differently due to differences in the perceived degree of closeness of relationships around the core of resources or information they own or hold ( Vveinhardt and Bendaraviciene, 2022 ). The difference in organizational climate is an organizational climate in which individuals treat members of the organization differently due to differences in perceived closeness.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…A study conducted by Tasdemir et al (2017) revealed that favouritism based on family relationships fosters a sense of distrust within businesses and diminishes employees' affective organisational commitment. Similarly, Vveinhardt & Bendaraviciene (2021) identified in their research that the perception of nepotism negatively impacts employees' trust perception, subsequently leading to reduced job satisfaction, performance, and affective organisational commitment. Furthermore, Han et al (2010) highlighted the significance of employing objective criteria and fostering transparent communication to enhance employees' affective organisational commitment.…”
Section: Introductionmentioning
confidence: 99%
“…Nepotism, favoritism, and cronyism are understudied locally and globally (Arasli and Tumer, 2008;Ombanda, 2018). Further research is needed to determine how these events relate to these factors at institutions worldwide (Vveinhardt and Sroka, 2020;Vveinhardt and Bendaraviciene, 2022).…”
Section: Introductionmentioning
confidence: 99%